Analysis Of Comparison The Stock Price At PT. Bank Tabungan Negara (Persero) Tbk, Before And After Applying The E-Blink - Nana Andani Darmawan Andani Darmawan (IAIN Manado, 2018)
Abstract This study aims to find out and analyze stock prices before and after the existence of E-Blink products at PT. Bank Tabungan Negara (Persero) Tbk. The sample used in this study is the closing stock price 30 days before and 30 days after the E-Blink product. The analytical method used Paired Sample t Test with the help of SPSS version 21.0. Hypothesis testing used statistics to analyze changes in stock prices of PT. Bank Tabungan Negara (Persero) Tbk with a significance level of 5%. The results showed that there were significant stock price differences before and after the E-Blink at PT. Bank Tabungan Negara (Persero) Tbk. This indicates the existence of information that is considered positive for investors with the existence of E-Blink products that will increase profits owned by the company and dividends for shareholders or investors. Keywords : Stock Price, E-Blink